Dextroamphetamine Treatment in Children With Hypothalamic Obesity - van Schaik, Jiska; Welling, Mila S.; de Groot, Corjan J.; van Eck, Judith P.; Juriaans, Alicia; Burghard, Marcella; Oude Ophuis, Sebastianus B. J.; Bakker, Boudewijn; Tissing, Wim J. E.; Schouten-van Meeteren, Antoinette Y. N.; van den Akker, Erica L. T.; van Santen, Hanneke M. (Frontiers in Endocrinology, 2022)
Introduction Hypothalamic obesity (HO) in children has severe health consequences. Lifestyle interventions are mostly insufficient and currently no drug treatment is approved for children with HO. Amphetamines are known for their stimulant side-effect on resting energy expenditure (REE) and suppressing of appetite. Earlier case series have shown positive effects of amphetamines on weight in children with acquired HO. We present our experiences with dextroamphetamine treatment in the, up to now, largest cohort of children with HO. Methods A retrospective cohort evaluation was performed of children with HO treated with dextroamphetamine at two academic endocrine pediatric clinics. Off-label use of dextroamphetamine was initiated in patients with progressive, therapy-resistant acquired or congenital HO. Anthropometrics, REE, self-reported (hyperphagic) behavior and energy level, and side effects were assessed at start and during treatment. Results Nineteen patients with a mean age of 12.3 ± 4.0 years had been treated with dextroamphetamine. In two patients, ΔBMI SDS could not be evaluated due to short treatment duration or the simultaneous start of extensive lifestyle treatment. Mean treatment duration of the 17 evaluated patients was 23.7 ± 12.7 months. Fourteen patients (n = 10 with acquired HO, n = 4 with congenital HO) responded by BMI decline or BMI stabilization (mean ΔBMI SDS of -0.6 ± 0.8, after a mean period of 22.4 ± 10.5 months). In three patients, BMI SDS increased (mean ΔBMI SDS of +0.5 ± 0.1, after a mean period of 29.7 ± 22.6 months). In 11 responders, measured REE divided by predicted REE increased with +8.9%. Thirteen patients (68.4%) reported decreased hyperphagia, improvement of energy level and/or behavior during treatment. Two patients developed hypertension during treatment, which resulted in dosage adjustment or discontinuation of treatment. Twelve children continued treatment at last moment of follow-up. Conclusion In addition to supportive lifestyle interventions, dextroamphetamine treatment may improve BMI in children with HO. Furthermore, dextroamphetamines have the potential to decrease hyperphagia and improve resting energy expenditure, behavior, and energy level. In patients with acquired HO, these effects seem to be more pronounced when compared to patients with congenital HO. Future studies are needed to support these results.